Cophylogenetic relationships between Dactylogyrus (Monogenea) ectoparasites and endemic cyprinoids of the north‐eastern European peri‐Mediterranean region. (15th November 2019) - Benovics, Michal; Desdevises, Yves; Šanda, Radek; Vukić, Jasna; Šimková, Andrea
Abstract: The study of host–parasite coevolution is one of the cornerstones of evolutionary biology. The majority of fish ectoparasites belonging to the genus Dactylogyrus (Monogenea) exhibit a high degree of host specificity. Therefore, it is expected that their evolutionary history is primarily linked with the evolutionary history of their cyprinoid fish hosts and the historical formation of the landmasses. In the present study, we used a cophylogenetic approach to investigate coevolutionary relationships between endemic Cyprinoidea (Cyprinidae and Leuciscidae) from selected regions in southern Europe and their respective Dactylogyrus species. A total of 49 Dactylogyrus species including endemic and non‐endemic species were collected from 62 endemic cyprinoid species in the Balkan and Apennine Peninsulas. However, 21 morphologically identified Dactylogyrus species exhibited different genetic variants (ranging from 2 to 28 variants per species) and some of them were recognized as cryptic species on the basis of phylogenetic reconstruction. Phylogenetic analyses revealed several lineages of endemic and non‐endemic Dactylogyrus species reflecting some morphological similarities or host affinities. Using distance‐based and event‐based cophylogenetic methods, we found a significant coevolutionary signal between the phylogenies of parasites and their hosts. In particular, statistically significant links were revealed between Dactylogyrus species of Barbini (Cyprinidae) and their hosts belonging to the genera Aulopyge, Barbus and Luciobarbus . Additionally, a strong coevolutionary link was found between the generalist parasites D. alatus, D. sphyrna, D. vistulae, and their hosts, and between Dactylogyrus species of Pachychilon (Leuciscidae) and their hosts. Cophylogenetic analyses suggest that host switching played an important role in the evolutionary history of Dactylogyrus parasitizing endemic cyprinoids in southern Europe. We propose that the high diversification of phylogenetically related cyprinoid species in the Mediterranean area is a process facilitating the host switching of specific parasites among highly diverse congeneric cyprinoids. Abstract : We used the cophylogenetic approach to investigate coevolutionary relationships between endemic cyprinoids from the Apennine and Balkan Peninsulas, and their respective Dactylogyrus species. Using distance‐based and event‐based cophylogenetic methods, we found significant coevolutionary signal between phylogenies of the parasites and hosts. Out of 138 host‐parasite individual links, 65 contributed significantly to the global cophylogenetic structure ( p  < .05). Results of the event‐based cophylogenetic analyses suggest that Dactylogyrus speciation is primarily driven by duplication followed by host‐switching.